Beyond shariah compliance: Malaysia’s Islamic economy and the unfinished pursuit of Maqasid al-Shariah - Mukhtar Idris Abu Bakr Adam; Muhammad Ali; Abdoulrahman Aljounaidi (Journal of Islamic Economic Insights, 2026)
Malaysia occupies a singular position in the global Islamic economy: for more than a decade, it has topped the Global Islamic Economy Indicator, having assembled the one of the world’s most complete institutional ecosystems for Islamic finance, halal production, and Shariah governance (DinarStandard, 2024). As an opinion and conceptual article, this paper develops a critical argument based on recent indexed scholarship, policy documents, and institutional reports rather than primary empirical data. Malaysia’s success has produced a paradox. The maturation of a dual banking system, a deep sukuk market, and an integrated halal complex has been achieved largely through operational convergence with conventional finance, so that Shariah compliance—the avoidance of prohibited forms—has advanced far more rapidly than the realization of Maqasid al-Shariah, the higher socioeconomic objectives that give Islamic economics its moral purpose (Asutay, 2025; Mergaliyev et al., 2021). Drawing on recent Scopus- and Web of Science–indexed scholarship, this study characterizes the “substance gap,” appraises Value-Based Intermediation as a corrective policy architecture, and evaluates the reintegration of Islamic social finance and the sustainability agenda. It contends that the next phase of Malaysian leadership must pivot from compliance-based competitiveness to impact-based authenticity and cautions that instruments such as green sukuk and Environmental, Social, and Governance (ESG) alignment risk becoming a rebranding exercise unless anchored in substantive Maqasid reasoning.